Problem-Based Learning: An Experiential Strategy for English Language Teacher Education in Chile (2017)
The Chilean education system requires English language teachers to be equipped with non-conventional teaching strategies that can foster meaningful learning and assure successful learners’ performances in diverse and complex settings. This exploratory, descriptive, research study aimed at discovering the perceptions of 54 pre-service teachers about the impact of a problem-based learning activity in the development of key competencies, including higher order thinking skills and reflective, research, knowledge transfer/integration, social, and self-management skills. Groups of participants chose a made-up, ill-structured problem which combined language teaching and socio-cultural issues, and devised holistic solutions. Findings suggest a comprehensive impact on the first four skills, but a limited impact on social and self-management skills.